PERSEPSI SISWA TENTANG PENERAPAN KESEHATAN DAN KESELAMATAN KERJA PADA PRAKTEK BATU DAN BETON SISWA KELAS X JURUSAN KONSTRUKSI BATU DAN BETON SMK NEGERI 1 PARIAMAN - 2010-2016, Adi Rama Prasetyo (Universitas Negeri Padang, 2018)
Abstract—The backgroud of this research is many accident occured during practicing stone and concrete subject. Based on accident occured this research answered the perception of student of SMK Negeri 1 Pariaman grade X Konstrusi Batu dan Beton against to the application during practicing. This is descriptive research. With number of sample is 22 students using technique of Total Sampling, that sampling with equal amount with population. The data collected using questionnaires with Likert scale consist of 5 answers and 34 items of statement. Technique data analysis used by interpreting achievement scores of respondents from each indicator.The result of the research shows that there are perceptions of Grade X students of Konstruksi Batu dan Beton on the application of occupational health and safety of the four indicators that has the largest percentage in the indicator material safety and the medium category is 50%.Keywords:Perception, Health and safety